Enhancing Critical Thinking and Self Directed Learning through Integration of Digital Competence and Didactic Strategy in Higher Education - Inayati, Nurul Latifatul; Al Mubarok, Fahmi Ulum; Rohmani, Annas Fajar (Journal of Interdisciplinary Studies in Education, 2026)
The rapid digital transformation of higher education, accelerated by the COVID-19 pandemic, has exposed a persistent misalignment between digital competence and pedagogical practice, limiting the development of critical thinking and self-directed learning. This qualitative descriptive study investigates how digital technologies and didactic strategies are integrated in practice. Data were collected through interviews, observations, and document analysis involving lecturers and students, and analyzed thematically. Findings reveal disparities in digital proficiency, limited use of advanced tools, and inconsistent implementation of learner-centered approaches. However, integrating digital technologies with project-based learning and peer assessment enhances problem-solving, communication, and metacognitive skills. The study highlights the importance of digital–didactic alignment, emphasizing the need for continuous professional development, institutional support, and curriculum redesign to foster effective, learner-centered digital learning environments.